2022
DOI: 10.1108/oir-12-2021-0655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the elevation of authoritative health content online during the COVID-19 pandemic

Abstract: PurposeTo respond to the COVID-19 “infodemic” and combat fraud and misinformation about the virus, social media platforms coordinated with government healthcare agencies around the world to elevate authoritative content about the novel coronavirus. These public health authorities included national and global public health organisations, such as the Centers for Disease Control and Prevention (CDC) and the World Health Organisation (WHO). In this article, the authors evaluate the effectiveness of this strategy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, the results of this study indicate that information resources at the government level do not meet the expected standard of providing quality transgender health information. This result accepting the findings of Walsh et al (2023) and they revealed that although most survey respondents recognized credible health information on the internet, there were substantial concerns regarding the trustworthiness of information from government healthcare agencies and public health authorities online.…”
Section: Transgendersupporting
confidence: 85%
“…However, the results of this study indicate that information resources at the government level do not meet the expected standard of providing quality transgender health information. This result accepting the findings of Walsh et al (2023) and they revealed that although most survey respondents recognized credible health information on the internet, there were substantial concerns regarding the trustworthiness of information from government healthcare agencies and public health authorities online.…”
Section: Transgendersupporting
confidence: 85%
“…The data showed that 3 in 4 British and 2 in 3 Americans were willing to receive coronavirus disease 2019 (COVID-19) vaccine, a quarter of people in the United States, Germany and France were hesitant about or squarely against getting the COVID-19 vaccine (Kantar, 2021). This poll, along with previous studies, demonstrated the extraordinary predicament that the global health-care system is facing, and the knife-edge that public health experts have been walking (Walsh et al, 2022). Vaccine hesitancy is a threat to the global recovery from the historical pandemic and also to the well-being of the entire population.…”
Section: Introductionmentioning
confidence: 72%
“…At the corporate level, the advertising sector and online platforms came to an agreement on a "Code of Practice on Disinformation" [35] to combat false information. Thus, major tech companies introduced warnings about false information, automated fact-checking, and tools for users to tag false news manually [36][37][38]. And social media industry leaders, some now united under Meta Platforms, Inc., expressed their agreement to fight misinformation with the release of a joint statement on combating fake news in 2020 [39].…”
Section: Introductionmentioning
confidence: 99%